SEEKING AND EVALUATING THE REGULATIONS OF INDONESIA’S EXCLUSIVE ECONOMIC ZONE - Ida Kurnia; Imelda Martinelli (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2016)
Regulation is the cornerstone for utilizing marine fisheries resources, and thus Indonesian Government had implemented its Constitution as basic laws and rules. Those regulations need further elaboration. Therefore, Indonesian Government established sets of laws related to the utilization of marine fisheries resources, and in its implementation, those laws and regulations should never deviate from the Constitution of the Republic of Indonesia. The utilization of marine fisheries resources in Indonesia’s Exclusive Economic Zone enables the possibility of cooperation and colaboration with other countries. Therefore, Indonesia is required to seek by evaluating and complementing the laws in accordance with its Constitution. Pengaturan merupakan landasan utama pemanfaatan sumber daya perikanan, Indonesia telah menyiapkan aturan dasar yaitu Landasan Konstitusional. Pengaturan tersebut perlu penjabaran lebih lanjut. Oleh karena itu Indonesia membentuk aturan-aturan yang terkait dengan pemanfaatan sumber daya ikan dan dalam implementasinya aturan tersebut tidak boleh menyimpang dari aturan yang paling dasar. Pemanfaatan sumber daya ikan di Zona Ekonomi Eksklusif adalah pemanfaatan yang memungkinkan adanya pemanfaatan berbagi dengan negara lain maka Indonesia dituntut untuk segera dapat mencari dengan cara mengevaluasi dan melengkapi aturan sesuai dengan Landasan Konstitusional.